Canadian Justice/Indigenous (In)Justice: Decolonization and the Canadian Criminal Justice System - Giannetta, Robert (Journal for Social Thought, 2021)
Canada’s criminal justice system (CJS) is plagued with issues from the overrepresentation of Indigenous peoples to annual expenditures totalling billions of dollars. To alleviate these problems, there has been a push to reform the CJS to better suit its objective to rehabilitate and reintegrate offenders, such as diversionary courts, increased use of community supervision, and culturally-specific programming. However, reformist movements are not doing enough to push the boundaries of criminal justice reform. Crafting policy solutions, which remain within the scope of the current carceral landscape, stifles all discourse that calls for fundamental change. Incrementally reforming the CJS forces public policy to tweak problematic aspects of the model but does not challenge the overall societal and political purpose of the justice system. Ultimately, the reformist approach to the CJS maintains the status quo, which disproportionally harms Inuit, Métis and First Nations people who have historically been over-represented in the CJS. This is because the CJS is deeply rooted in colonialism and serves as a mechanism for the continued subjugation and oppression of Indigenous peoples. Reforming the justice system to become more culturally competent for Indigenous peoples is merely a façade to prevent questions of state sovereignty, legitimacy, and Canada’s colonial origins. True reform calls for the decolonization of the CJS. In this paper, to achieve the Truth and Reconciliation Commission’s Call to Action No. 42 (i.e., the recognition and implementation of Indigenous justice systems), it will require both analysis and discussion of Canada’s past, present and future.